(3QFjS GdLeghQjI aj GdfXGe GdOSJhQj GdeUQj (B: s (3ENJjGQg (B- (3SdWGJg (B/ s - (3aDGO YHO GdfHi MSf aQLs; (3CMeO ceGd CHh GdeLO (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s, 1995)
(3JHOC gPg GdQSGdI HHGH JegjOj Yf GdShGHb GdSjGSjI hGdOSJhQjI GdJj eQ HgG fXGe GdMce aj eUQ, Ke GdbSe GdChd Yf GNJjGQ QFjS GdLeghQjI, hGdbSe GdKGfj Yf SdWGJ QFjS GdLeghQjI(B.s
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B1995.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI UaMGJ (B591 - 602.s
Keywords: (3GdbGfhf GdOSJhQjs; (3cjajI GNJjGQ QFjS GdLeghQjIs; (3cjajI Jchjf eLdS GdTYHs; (3aJQI GdQFGSIs; (3SdWGJ QFjS GdLeghQjIs; (3fGFH GdQFjSs; (3GdGSJaJGAs; (3MGdI GdWhGQFs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs